Colonization of India and Muslims response through Socio-religious movements - Yasmeen, Razia (Al-Irfan, 2022)
This Article argues that during the colonial period, Muslims of India faced challenges but this period also produced notable individuals who have overcome barriers and contributed in the social, religious, and political resurgence of India's Muslims . In response to colonial tyranny, Muslims in South Asia have had three reactions: rejection, acceptance, and integration, as well as practical usage. During the British military and political domination over India, various Islamic socio-religious movements arose. They not only influenced Indians, but also sparked a movement of nationalism among India's Muslims. In this article, we looked at the Muslim socio-religious movements that affected Indian Muslim society throughout the colonial rule in the nineteenth and twentieth centuries. This article examines the responses of several Indian Muslims socio-religious movements to Colonial oppression in the Indo-Pak peninsula. It argues that socio-religious organizations provided new perspectives to religion throughout the British regime. Muslims had a greater sense of social service as movements took up disaster relief, school construction, orphanages, and hospitals. This study refutes the generally accepted view that Islam remained static in nineteenth-century India and that considerable cultural change occurred only as a result of the acceptance of Enlightenment ideals.